Comparative genomic analysis of Mycobacterium tuberculosis in lung and meningeal tuberculosis / Syakirah Nurizzati Mohamad Hood - Syakirah Nurizzati , Mohamad Hood (2019)
Tuberculosis is a serious lung disease that has infected a large human population throughout the world. Most cases of tuberculosis in humans are primarily caused by Mycobacterium tuberculosis. Tuberculosis cases worldwide mainly affect the lungs, but Mycobacterium tuberculosis also causes death by invading the central nervous system, or also known as meningeal tuberculosis. Although the percentage of infection is low, this disease has raised concerns as it is more lethal than lung tuberculosis. The purpose of this study is to identify the genomic differences between the strains that have been isolated from the lung and the cerebrospinal fluid. The dataset of the DNA of both samples that have been previously sequenced is obtained from online database. The lung strain that is used for this study is H37Rv (Genbank ID: NC_000962), which is known as the most common Mycobacterium tuberculosis strain that infects patients. The Mycobacterium tuberculosis strain from the brain used for this study is strain TKK_04_0158 (Genbank ID: KK324934). The result of this analysis has shown the differences of the genes presented in both strains, which has led to the discovery of the unique gene of each strain. The findings of this study will benefit the medical treatment of meningeal tuberculosis as it will provide an opportunity to develop or improve drugs and vaccine.